Analysis of Tone Pronounciation in Beginner-Level Students of Mandarin Language Education Program at Semarang State University (UNNES) Using PRAAT Program Assistance - Fajriyah, Laeli; Agwinanda, Almira; Marsuki, Ria Riski (Universitas Negeri Semarang, 2025)
Mandarin Chinese is one of the languages that uses a tonal system, errors in tone pronunciation can lead to differences in meaning. Pronunciation differences can be directly perceived by experts, but with the advancement of technology today, detailed differences can be observed through sound processing programs or applications. This study uses PRAAT as an auxiliary sound processing tool, which can display pitch curves of voices and show the frequencies used to analyze tone pronunciation. The subjects of this study are undergraduate students from the class of 2024 of the Mandarin Language Education program at UNNES, at the beginner level. The study uses a descriptive quantitative approach, with the tone pronunciation analysis results of native speakers used as a comparison to the students' tone pronunciations. Data collection techniques in this research include observation, recording field notes, and documentation. The results of this study show that 19.19% of students pronounced tone 1 with a rising frequency, 22.7% of students pronounced tone 2 with a low frequency difference, making it sound similar to tone 1, and more than 93% of students pronounced tone 4 with a high frequency spike. This research is expected to provide a reference for developers of technology-based language learning applications to improve pronunciation analysis features. In addition, it is hoped that this research can contribute to the field of phonetics and serve as a reference for similar studies.